Сарнилын пикийг ашигласан тулгуур параметрын арга - Н, Гансүх; П, Зузаан; Б, Далхсүрэн (Scientific transaction of the National University of Mongolia. Physics, 2022)
Instead of using the complete set of fundamental parameters for solving matrix effects in quantitative energy dispersive x-ray fluorescence analysis, some of them, such as excitation and detection efficiency and dependence of Compton and Reylaeigh scattered intensities on sample composition, were determined from a set of standards such as chemical compounds and pure elements. In this way all fundamental parameters except mass absorbtion coefficients were removed from the calculation procedure, which results in a much simpler formalism. the computer program based on this principle and described in this paper is relatively simple and, can run even on small computers, while the overall error can be kept in the range of few percent.